Machine Health Monitoring Using An Innovative Mechanical Approach - Romayasari, Vera; Auliana, Sigit; Aryono, Gagah Dwiki Putra (LPPM STIKOM Tunas Bangsa, 2024)
In today's world, machines are essential in daily life, requiring efficient and safe operation. Tools have been developed to assess machine health by monitoring power usage, temperature, noise, and vibrations. Anomalies in these parameters can indicate potential defects. FFT analyzers, commonly used for vibration measurement, are often too costly for small businesses and may lack the ability to measure speed, temperature, or power usage. This project aims to create a low-cost alternative for health monitoring systems, capable of measuring vibrations, noise, temperature, speed, and power consumption. Integrating an Arduino Uno R3 with sensors and a MATLAB 2018b GUI provides an affordable solution, catering to small firms unable to invest in expensive FFT analyzers